Construction and application of a decision support tool for determining venous access in breast cancer chemotherapy patients - Wu, Meng; Liao, Yan‐yan; Lin, Zheng (Journal of evaluation in clinical practice, 2025)
Objective To construct a decision support tool for determining venous access in chemotherapy of breast cancer. Methods A decision support tool for determining venous access was developed through semi‐structured interviews, literature analysis, expert inquiry, and user adaptation. The subjects of the study were breast cancer patients with chemotherapy who planned to have deep vein catheterization in a Grade IIIA hospital in Nanjing from August to December 2023. The enrolled patients were then divided into the control group and the intervention group, with 44 cases in each group. The control group received routine pre‐catheterization interviews, while the intervention group used the decision support tool on this basis. Further comparison was conducted on the willingness of and actual participation in decision‐making, decisional conflict, decision‐making satisfaction, and decision regret between the two groups using t‐test and chi‐square test. Results This study constructed a decision support tool for determining venous access in chemotherapy of breast cancer, including 8 primary indicators and 40 secondary indicators. The intervention group actually participated in treatment decisions more than the control group, and the intervention group was more willing to participate in treatment decisions (p < 0.05). Furthermore, the intervention group had significantly higher degrees of actual participation in decision‐making and satisfaction with decision‐making compared to the control group (p < 0.05); while the former group had significantly lower decisional conflict, decision regret at 1 month and 3 months after discharge than those in the latter group (p < 0.05). Conclusion The decision support tool for determining venous access in chemotherapy of breast cancer is scientific and practical to promote patient participation in decision‐making, reduce decisional conflicts, improve decision‐making quality, and achieve joint decision‐making between doctors and patients.